Tylko tchórze i kobiety pragną pokoju. Wokół satyry Adolfa Nowaczyńskiego "Wojna wojnie" - Bielas, Bartłomiej (Zagadnienia Rodzajów Literackich, 2025)
The article presents an analysis of Adolf Nowaczyński’s 1927 comedy Wojna wojnie. Warchoł i Miroluba. Komedja Arystofanesoska [War on War. Warchoł and Miroluba. An Aristophanic Comedy]. The play is a loose paraphrase of Aristophanes’ Lysistrata and The Knights. The article places particular emphasis on how Wojna wojnie expresses fear of pacifism and female power. Using satire, Nowaczyński criticizes the Sanation government and mocks pacifist attitudes and women’s emancipation efforts, which he perceives as a threat to “masculine” strength and national identity. In the imagination of the National Democracy circles with which Nowaczyński was affiliated, pacifism is associated with Jewish conspiracies and the feminization of society, and is seen as a sign of national weakness. By exaggerating and ridiculing these social phenomena, Nowaczyński’s comedy becomes an expression of the era’s anxieties — that progressive movements might undermine the moral and cultural foundations of Poland. The article also uses the comedy as a pretext for a broader discussion of pacifism in interwar Poland, examining how it was perceived, debated, and criticized within right-wing public discourse. In Wojna wojnie, pacifism does not appear as a noble ethical stance but as a dangerous phenomenon that threatens national strength and is equated with submission and the betrayal of traditional values such as strength, honor, and duty to the homeland.